Penerapan Konsep Metafora Pada Pusat Wisata Edukasi Geopark Batur Di Kintamani : bahasa indonesia - Ni Putu Nadya Darma Putri; I Nyoman Nuri Arthana; I Gede Surya Darmawan; Ida Bagus Gede Parama Putra; Km. Deddy Endra Prasandya Prasandya (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2024)
Batur Geopark is one of the Geoparks that has been registered as a UNESCO Global Geopark. However, public interest in knowledge related to geoparks is still low, especially in terms of education, therefore it is necessary to develop a more modern and attractive batur geopark educational tourism center to increase public interest and knowledge related to geoparks, so the application of the concept of metaphor and contemporary architectural themes was chosen. so that in the process using several concepts including zoning concepts, entrance concepts, mass concepts, circulation concepts, outdoor space concepts, contemporary architectural themes, so that in the process using several concepts including zoning concepts, entrance concepts, mass concepts, circulation concepts, outdoor space concepts, indoor space concepts, facade concepts, structural concepts and utility concepts, the purpose of this development is to provide a fun and educational place for people who will come to the facility to get to know the natural and cultural wealth that exists in the geopark.